The Effect of Whatsapp and Zoom on Knowledge and Attitudes about Dangerous Signs of Pregnancy During COVID-19 - Asih, Suci; Agushybana, Farid; Shaluhiyah, Zahroh (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
The dangerous sign of pregnancy can occur unpredictably, especially in the third trimester. In the COVID-19 pandemic, pregnant women are often worried about antenatal checks up because there is a potential for COVID-19 transmission, and education for pregnant women cannot be carried out because of social distancing, especially in red zone areas. This study is to measure the effect of Whatsapp and Zoom media on the knowledge and attitude of pregnant women about the dangerous sign of pregnancy. This study used a quantitative approach with quasi-experimental research with a purposive sampling technique. Samples were taken with a proportion of 1:1 with a total of 32 respondents in each group. The measuring instrument used a questionnaire that has been tested for validity dan reliability. Data analysis used Friedman Test. The results of the analysis showed that there was an effect of Whatsapp and Zoom media on knowledge (p=0,0001) and attitude (p=0,0001) of pregnant women about the dangerous sign of pregnancy. Difference average score increase in the intervention group for knowledge dan attitude variables. Giving health promotion media through Whatsapp and Zoom media has been proven to increase the knowledge and attitude of pregnant women about the dangerous sign of pregnancy and it can be applied in health services during the COVID-19 pandemic. Abstrak: Tanda bahaya kehamilan dapat terjadi tidak terduga, terutama pada trimester ketiga. Di masa pandemi COVID-19 ibu hamil sering kali khawatir dengan pemeriksaan kehamilan karena berpotensi menularkan COVID-19 dan edukasi kepada ibu hamil tidak bisa dilakukan karena social distancing terutama di kawasan zona merah. Penelitian ini bertujuan untuk mengukur pengaruh media Whatsapp dan Zoom terhadap pengetahuan dan sikap ibu hamil tentang tanda bahaya kehamilan. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis penelitian quasy-experimental dengan teknik purposive sampling. Sampel diambil dengan proporsi 1:1 dengan jumlah 32 responden pada setiap kelompok. Alat ukurnya menggunakan angket yang telah diuji validitas dan reabilitasnya. Analisis data menggunakan Uji Friedman. Hasil analisis menunjukkan bahwa ada pengaruh media Whatsapp dan Zoom terhadap pengetahuan (p=0,0001) dan sikap (p=0,0001) ibu hamil tentang tanda bahaya kehamilan. Selisih peningkatan skor rata-rata pada kelompok intervensi untuk variabel pengetahuan dan sikap. Pemberian media promosi kesehatan melalui media Whatsapp dan Zoom terbukti dapat meningkatkan pengetahuan dan sikap ibu hamil tentang tanda bahaya kehamilan dan dapat diterapkan dalam pelayanan kesehatan di masa pandemi COVID-19.